Hope and Tragedy: insights from religion in the philosophy of Paul Ricoeur - Daughton, Amy (European Journal for Philosophy of Religion, 2019)
The trajectory of Paul Ricoeur’s thought from the fallible to the capable human person offers a hopeful vision of human nature constitutive of our shared political life. Yet, by necessity, hope arises in response to the tragic, which also features in Ricoeur’s work at the existential and ethical levels. At the same time hope and tragedy represent concepts at the limit of philosophical reasoning, introducing meeting points with religious discourse. Exploring those meeting points reveals the contribution of religious thinking to the understanding of hope and tragedy and establishes Ricoeur’s political thinking as ultimately shaped by their interplay.